When are glucocorticoids harmful for the eye? - Bartuzi-Łopusiewicz, Lilianna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The glucocorticosteroids are medications showing high effectiveness in the treatment of many systemic diseases having an immunological basis, in particular of allergic diseases. Cataract and glaucoma are serious complications of taking local and general GKS. Both these diseases cause considerable visual impairment, and glaucoma can lead to permanent damage of the optic nerve. The adverse reactions depend on several factors: the kind of preparation, the dose, the duration of treatment of disease, and individual factors including age, sex, genetic predisposition and interaction with different medications. Glaucoma or lenticular changes can develop even after a short period of taking GKS, while in some patients long therapy does not provoke changes. The value of the medication depends not only on the effectiveness of its medicinal properties, but also on the essential aspect of the safety of its application. The doctor should have knowledge on the subject of dangers connected with it.